2007
DOI: 10.1158/0008-5472.can-07-1133
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Profiling in Liposarcomas Reveals Genetic Alterations Common to Specific Telomere Maintenance Mechanisms

Abstract: Telomere attrition ultimately leads to the activation of protective cellular responses, such as apoptosis or senescence. Impairment of such mechanisms can allow continued proliferation despite the presence of dysfunctional telomeres. Under such conditions, high levels of genome instability are often engendered. Data from both mouse and human model systems indicate that a period of genome instability might facilitate tumorigenesis. Here, we use a liposarcoma model system to assay telomere maintenance mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…S1B in the supplemental material), indicating the clinical significance of HMGA2-mediated hTERT modulation in the contribution of tumor progression. Consistently with our report, Johnson et al have identified a correlation between the chromosomal amplification of 12q14.3, where HMGA2 is localized, and the activation of hTERT to stabilize the telomeres in liposarcomas (30). Moreover, a number of studies have demonstrated that higher hTERT mRNA levels in breast cancers were associated with a high tumor grade, increased invasiveness, and poor prognosis, such as recurrent disease or decrease in overall survival rate (24,41,49).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…S1B in the supplemental material), indicating the clinical significance of HMGA2-mediated hTERT modulation in the contribution of tumor progression. Consistently with our report, Johnson et al have identified a correlation between the chromosomal amplification of 12q14.3, where HMGA2 is localized, and the activation of hTERT to stabilize the telomeres in liposarcomas (30). Moreover, a number of studies have demonstrated that higher hTERT mRNA levels in breast cancers were associated with a high tumor grade, increased invasiveness, and poor prognosis, such as recurrent disease or decrease in overall survival rate (24,41,49).…”
Section: Discussionsupporting
confidence: 92%
“…A recent study also has shown that telomerase inhibition using the potent telomerase inhibitor GRN163L depletes cancer stem cells, rare drug-resistant cancer cell subsets proposed to be responsible for the maintenance and recurrence of cancer and metastasis, in breast and pancreatic cancer cell lines (31). These reports further support the importance for connecting HMGA2 expression to hTERT modulation (30).…”
Section: Discussionmentioning
confidence: 71%
“…One immortalized human cell line, C3-cl6, maintained short and homogeneous telomeres in the absence of telomerase (10). These studies, in addition to many telomerasenegative tumors that have been shown to lack long and heterogeneous telomeres (9,(12)(13)(14)(15), support the prospect of an ALT mechanism where telomeres are normal in length rather than long and heterogeneous.…”
Section: Pot-2 Represses a Distinct Form Of Alt With Telomeres Of Normalmentioning
confidence: 64%
“…Furthermore, extensive analysis of telomerase activity and telomere length from primary human tumor samples has revealed that certain telomerase-negative tumors possess long and heterogeneous telomeres, defined as alternative lengthening of telomeres (ALT) tumors (9). However, the majority (81/108) of primary tumors lacking telomerase activity have telomeres of normal lengths (9,(12)(13)(14)(15). This subset of telomerase-negative tumors may have become neoplastic before exhausting their telomere repeat reserves (9, 16).…”
mentioning
confidence: 99%
“…We also note that some sample handling information is missing from the submission: although fresh freezing is specified in previous publications on the referenced part of the set provided by the Fox Chase Cancer Centre (Johnson et al, 2005(Johnson et al, , 2007, no information is given for the unpublished samples provided from other sources cited in the submission. This may be an important issue: it is essential to ensure that the main contributing factor to intergroup variation in microarray data is biological and not technical variance.…”
mentioning
confidence: 99%